COVID-19 vaccine uptake, reasons, and associated factors among older adults in Shenzhen, China - Pei Xie; XiuYuan Shi; Bin Zhu; Wenjing Zhao; Xiaoheng Li; Xuan Zou; Gang Liu; Xinxin Han (Taylor & Francis Group, 2023)
Evidence is limited on the actual uptake of the coronavirus disease 2019 (COVID-19) vaccine among older adults, especially those with chronic diseases, during the pandemic. To examine COVID-19 vaccine uptake, reasons, and associated factor among older adults, a cross-sectional survey was conducted between September 24 and October 20, 2021 among older adults aged 60 and above in Shenzhen, China. Logistic regression analysis was used to examine associations of COVID-19 vaccine uptake with sociodemographic characteristics, pneumonia vaccination history, and participation in health education activities among older adults and among those with chronic diseases. Of the 951 participants, 82.8% reported being vaccinated against COVID-19 during the study period, but this proportion was relatively lower among adults aged 80 and above (62.7%) and those with chronic diseases (77.9%). The top-rated reasons for not being vaccinated included doctors not recommending it due to underlying diseases (34.1%), not being ready for it (18.3%), and failure to make an appointment (9.1%). General older adults who were aged below 70, had a high school and above education, were permanent residents of Shenzhen, were with good health and had pneumonia vaccination history were more likely to take the COVID-19 vaccination. Yet, among older adults with chronic diseases, other than age and permanent residency status, health status was the only significant indicator of COVID-19 vaccine uptake. Our study added to evidence that health condition is the critical barrier to the actual uptake of the COVID-19 vaccine among Chinese older adults, especially those aged 80 and above and those with chronic diseases.